(untitled) (Global Journal of Science Frontier Research, 2012)
Weeds are considered as unwanted plants. However some weeds posses valuable pharmaceutical importance. Number of researchers combined this fact with an ethnobotanical approach. The present work reports, pharmaceutically important weeds from the common fields (Sorghum, Sugarcane, Maize, Wheat, Pulse Crop and wasteland)of Mohol Tahasil of Solapur district, Maharashtra state. 21 valuable weed species were collected from different fields of Mohol Tahasil and identified for their pharmaceutical source using standard literature and herbal pharmacopoeias. Ethnomedicinal and weed survey in this area was not much explored and hence the present investigation was taken up.